1996
DOI: 10.1111/j.1472-765x.1996.tb00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of antibiotic and metal resistance and plasmid Carriage in Aeromonas isolated from brown bullhead (latalurus nebulosus)

Abstract: Seventy-four strains of Aeromonas were isolated from skin, intestine, kidney and liver of 16 brown bullhead (Ictalurus nebulosus). All strains demonstrated multiple antibiotic resistance (MAR) with most strains resistant to rifampin (97O/o), novobiocin (96%) and vancomycin (85%). The minimum inhibitory concentration of eight metals to selected strains of Aeromonas revealed an apparent toxicity of chromium > copper > cadmium > nickel > mercury > zinc > cobalt > lead, based on the percentage of isolates sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
19
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 24 publications
7
19
0
3
Order By: Relevance
“…This is partially supported by Ansary et al (1992) and Son et al (1997). However, Pettibone et al (1996) have not reported any erythromycin resistant A. hydrophila strains. The variation in the drug resistance may well be related to the source of the A. hydrophila isolates and the frequency and type of antimicrobial agents prescribed for treating Aeromonas infections, e.g.…”
Section: Resultssupporting
confidence: 51%
See 4 more Smart Citations
“…This is partially supported by Ansary et al (1992) and Son et al (1997). However, Pettibone et al (1996) have not reported any erythromycin resistant A. hydrophila strains. The variation in the drug resistance may well be related to the source of the A. hydrophila isolates and the frequency and type of antimicrobial agents prescribed for treating Aeromonas infections, e.g.…”
Section: Resultssupporting
confidence: 51%
“…All the strains were resistant to methicillin, which was similar to the findings of Motyl et al (1985) who reported that all A. hydrophila strains of human origin were resistant to methicillin. In contrast, Pettibone et al (1996) observed that only 54% of the strains was resistant to this antibiotic. However, Kampfer et al (1999) reported that no significant differences could be observed between clinical and non-clinical Aeromonas isolates, although the clinical isolates showed a few more positive results with respect to antibiotic resistance.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations